2012
DOI: 10.1126/science.1226860
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin/Oxytocin-Related Signaling Regulates Gustatory Associative Learning in C. elegans

Abstract: Vasopressin- and oxytocin-related neuropeptides are key regulators of animal physiology, including water balance and reproduction. Although these neuropeptides also modulate social behavior and cognition in mammals, the mechanism for influencing behavioral plasticity and the evolutionary origin of these effects are not well understood. Here, we present a functional vasopressin- and oxytocin-like signaling system in the nematode Caenorhabditis elegans. Through activation of its receptor NTR-1, a vasopressin/oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
190
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 62 publications
5
190
0
1
Order By: Relevance
“…These pNPs regulate several aspects of physiology, including sexual behavior and reproduction (GnRH, achatin, oxytocin, and GnIH/SIFamide), diuresis (CRF/diuretic hormone, calcitonin, and vasopressin), gut and heart activity (achatin, luqin, and orcokinin), pain perception (opioid), and food intake (NPY, kinins, neuromedin-U, galanin/allatostatin-A, and orexin/allatotropin). These pNPs may have originated concomitantly with the origin of a complex bilaterian body plan having a through gut with novel controls for food intake and digestion, excretory and circulatory systems, light-controlled reproduction (50), a centralized nervous system (76), complex reproductive behavior (77,78), and learning (79). The stable association of receptor-ligand families across bilateria revealed the long-term coevolution of receptor-ligand pairs.…”
Section: Resultsmentioning
confidence: 99%
“…These pNPs regulate several aspects of physiology, including sexual behavior and reproduction (GnRH, achatin, oxytocin, and GnIH/SIFamide), diuresis (CRF/diuretic hormone, calcitonin, and vasopressin), gut and heart activity (achatin, luqin, and orcokinin), pain perception (opioid), and food intake (NPY, kinins, neuromedin-U, galanin/allatostatin-A, and orexin/allatotropin). These pNPs may have originated concomitantly with the origin of a complex bilaterian body plan having a through gut with novel controls for food intake and digestion, excretory and circulatory systems, light-controlled reproduction (50), a centralized nervous system (76), complex reproductive behavior (77,78), and learning (79). The stable association of receptor-ligand families across bilateria revealed the long-term coevolution of receptor-ligand pairs.…”
Section: Resultsmentioning
confidence: 99%
“…Other examples of functional analogy between orthologous protostome and deuterostome PSs include the cholecystokinin/sulfakinin that are involved in satiety (22) in humans and worms, and GnRH and AKH that have analogous functions in reproduction in both humans and worms (20). Two recent studies (43,44) showed that a bona fide vasopressin system was present in C. elegans and that it might participate in ancient circuits that control adaptive reproductive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It will be particularly interesting in the future to study the function of these genes in the amphioxus and lophotrochozoan species to learn more about the conserved features of these vertebrate PSs. Recently, several PSs have been characterized in the nematode, including vasopressin (43,44). We give predictions for C. elegans peptides that had not been characterized to date, which include TK, DH31/Calc, SIFa, LK, luqin, and AstA, B, and C (Dataset S1).…”
Section: Discussionmentioning
confidence: 99%
“…Mutants worms lacking nematocin (an AVP/OT-related neuropeptide) or its receptor were subjected to an associative learning paradigm using a short-term gustatory plasticity assay (56). The results suggested that defects in the nematocin signaling cascade disrupted gustatory associative learning and the facilitated experience-driven modulation of sodium chloride chemotaxis.…”
Section: Oxytocin In Learning and Memorymentioning
confidence: 99%